Analyzing the Causes and Effects of Rural Landscape Changes: The Case of the Ordu Province of Eastern Black Sea Basin (Turkey) - Dikcinar Sel, Berna (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2021)
Building on the perspective that indigenousness of cultural landscapes must be protected, the present article studies the changes on landcover/landuse; one of the most important components of cultural landscapes. The aim is to provide data for future planning studies protecting cultural landscapes. This study is carried out in three stages. In the first stage, landcover is investigated in five time points (1990, 2000, 2006, 2012, and 2018), in four main categories (artificial surfaces, agricultural areas, forest areas, water bodies), and the changes are reported comparatively. In the second stage, examinations are detailed according to the first stage's results. Transitions among categories which led to significant changes, and the transition process is analyzed. Landscape Transition Matrix and transition intensities are calculated for three time points and two time periods. In the last stage, landcover transitions according to subclasses are analyzed. In the conclusions section, causes and effects of the changes are discussed. This study is providing detailed inputs to future solutions by incorporating the landcover categories among which the transitions occurred, periods of these transitions, and analyzing the intensity of the subclasses. The sample area selected is Ordu province in the Eastern Black Sea Region, where the climate with high precipitation, harsh topography, its forests, scattered settlement pattern, agricultural production, and migration activities differentiate among the Anatolian Peninsula. The results of the analyses are indicating that the landcover changes are against the agricultural and forest areas, and the problem lies within the uncontrolled expansion of hazelnut gardens.
Keywords: Cultural landscape; landscape changes; rural landscape; CULTURAL LANDSCAPES; MANAGEMENT; URBANIZATION; TUSCANY; Architecture